Enhancing Elementary Students' Reading Comprehension of Informational Texts Through Problem-Based Learning - Juliati, Siti; Afendi, Arief Hidayat; Sutisno, Aliet Noorhayati (Papanda Publisher, 2025)
Reading comprehension represents a fundamental cognitive process essential for academic success, yet many elementary students demonstrate significant challenges in understanding informational texts. Traditional lecture-based instructional approaches have proven insufficient in developing deep comprehension skills necessary for critical analysis and knowledge construction. This study investigated the effectiveness of Problem-Based Learning (PBL) methodology in enhancing reading comprehension among fifth-grade students studying Indonesian language informational texts. A classroom action research design following the Kemmis and McTaggart model was implemented over two instructional cycles at SDIT Global Islamic School Permata Ummi. Nineteen fifth-grade students participated in systematic PBL implementation involving real-world problem presentation, collaborative investigation, and solution development. Data collection utilized pre-cycle assessments, post-cycle evaluations, structured observations, and comprehensive documentation. Quantitative analysis employed percentage calculations to determine mastery rates and performance improvements. Substantial improvements were observed across all implementation phases. Student mastery rates increased from 47% in pre-cycle assessment to 68.42% in Cycle I and 94.7% in Cycle II, representing a 47.7% overall improvement. Class averages progressed from 78.42 to 88.31, demonstrating consistent enhancement in collective reading comprehension capabilities. The progression from Cycle I to Cycle II showed 26.28% improvement, exceeding established success criteria. The findings validate constructivist learning principles underlying PBL methodology, demonstrating that students effectively construct knowledge through guided problem-solving experiences. Results indicate that PBL addresses multiple reading comprehension dimensions simultaneously, including factual identification, inferential reasoning, main idea comprehension, and evaluative interpretation. The research provides empirical evidence for integrating critical thinking development with reading instruction, offering practical alternatives to traditional pedagogical approaches for enhancing elementary literacy education.